Evaluasi Dimensi Box Culvert pada Saluran Drainase Jalan Arteri Soekarno Hatta (Studi Kasus: Ruas Untung Surapati- Hajimena) - Aniessa Rinny Asnaning; Iskandar Zulkarnain (Jurusan Teknologi Pertanian, 2020)
Flow system engineering using box culvert had done in arterial road Soekarno Hatta section Untung Surapati-Hajimena, precisely on the Way Kandis river channel. As population growth, on the box culvertâ€™s upstream, had frequently been flooding when it rains with high intensity. It could predict that run off discharge was increased as an impact increasing runoff coefficient due to the growth of the built area in its upstream. It indicated that the box culvert dimension is not suitable to serve runoff discharge. Therefore the evaluation is needed to assess whether the dimension of box culvert was still capable of serving the flowing runoff discharge. The existing box culvert dimension could not serve the runoff discharge in 10, 20, and 25 year return periods are 10.13 m3/s, 11.07 m3/s, dan 11,37 m3/s.It was recommended to use precast concrete (n = 0.03)and 0.015 in slope.The evaluation shown that to serve runoff discharge in 10, 20, and 25 year return period, minimum needed box culvert with dimensions are 1.9 x 1.9 (m), 2.0 x 2.0 (m), and 2.0 x 2.0 (m). Refer to it, then recommended the dimension of box culvert is 2.0 x 2.0 m. It could install more than one with an adjustment dimension if the slope were difficult to reach in the recommended dimensionÂ Keywords: river, flood, discharge, box culvert.